Análisis sobre el manejo de la seguridad y salud industrial en las empresas de hipermercado, frente al nuevo virus pandémico COVID 19 en Colombia durante el año 2020 (2021)
Industrial safety and health at work, manages to be a fundamental part of any company, so much so that it has been put to the test with what is currently being presented, in which the pandemic is involved due to of COVID 19, which reiterates the importance of saving, caring for and protecting the lives of internal customers, work personnel. Faced with this new situation that the human being is facing, new protection measures must be taken in this area, which calls attention to investigate, due to the fact that it is a totally new issue for society, where intervention is even seen of the government in all this commercial process that companies carry out. In this way, the various policies, measures, risk management, planning and emergency preparation that both a large and a small company should have taken for these extracurricular reasons will be analyzed, as the virus has brought, in which the environment of workers in the labor market during the coronavirus in Colombia, evaluating and comparing this aspect in industries of the marketing sector with a multi-format strategy in managing hypermarkets, supermarkets with a supply structure or productive chain, thus highlighting the importance that this entails this whole procedure.